2021
DOI: 10.3390/ijerph18126604
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Patients’ Willingness to Pay for a Basic Outpatient Copayment and Medical Service Quality in Taiwan

Abstract: Patients might be willing to pay more to obtain better quality medical services when they recognize that high-level hospitals have better quality. However, published papers have not found solid empirical evidence to support this possibility. Therefore, the purpose of this study is to empirically investigate patients’ willingness to pay (WTP) for an outpatient copayment. The study aims to analyze the difference between the two WTP values: to implement a hierarchy of medical care and to improve the quality of me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 32 publications
(38 reference statements)
1
6
0
Order By: Relevance
“…Additionally, Hsu et al (2021) noted that the WTP is estimated to be greater than the premiums collected by insurers. 34 This disparity could be explained by insurance companies' failure to conduct studies on consumer behaviour. In other words, insurers typically base their policies on macro studies and theoretical foundations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, Hsu et al (2021) noted that the WTP is estimated to be greater than the premiums collected by insurers. 34 This disparity could be explained by insurance companies' failure to conduct studies on consumer behaviour. In other words, insurers typically base their policies on macro studies and theoretical foundations.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, teachers who were aware of the insurance had a 2.5-fold greater tendency to pay more than those who were not, according to a study conducted in Ethiopia. [32][33][34][35][36][37] The type of health insurance could explain these distinctions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MC payment is a sort of payout for sickness, illness, or injury diagnosis, cure, mitigation, treatment, or prevention, including checks and periodic exams [ 1 ]. The cost of MC is not regulated in the same way that other markets are and challenging to determine it [ 2 , 3 ]. Healthcare is one of the social security components in the domain of health and is vital for people's and society's well-being.…”
Section: Introductionmentioning
confidence: 99%
“…In almost all the studies noted that WTP for health care was far lower than the actual cost patients were required to pay of the service [ 23 , 24 ]. Majority of previous studies reported that socio-demographic factors like gender, age, socioeconomic status, and educational level had great role in influencing the WTP for MC [ 2 , 7 , 8 , [25] , [26] , [27] ].…”
Section: Introductionmentioning
confidence: 99%